Implementation Strategy Analysis of Network Security using dalo RADIUS and Pi-hole DNS Server to enhance Computer Network Security, Case Study: XYZ as a Fintech Company - Andika Davi Yudhistira; Ruki Harwahyu (Jurnal Indonesia Sosial Teknologi, 2024)
According to the annual report by the National Encryption Agency in 2023, Indonesia had the highest number of cyber-attack sources, with over 1 million attacks, which has increased quite rapidly compared to the last 3 years. Several online media platforms have reported incidents of this nature over the past three years. Among the 10 institutions implicated in the present incident, it has been confirmed that 6 of them are Fintech institutions. The incident's factors are various, including the user's lack of awareness who accessed an unofficial website outside the company's production website. This act ultimately proved to be detrimental to the company. Therefore, this study highlights the importance of RADIUS (Remote Authentication Dial-In User Service) as a comprehensive security tool that contributes to mitigating unauthorized access and strengthening network defenses against emerging threats. This research focuses on XYZ, a Fintech Company, using it as a case study. The main discussion in this paper focuses on utilizing the daloRADIUS server to resolve authorization concerns regarding network security. Pi-hole DNS Server is also used in this research to block access to illegal sites such as pornography and online gambling. The results of this research are proof of the success of a combination of daloRADIUS server components, RADIUS router, and Pi-hole DNS Server in blocking users who are detected accessing illegal sites and are also observed regarding the use of daloRADIUS Server resources in a usage range ranging from 10 active users to 300 active users.